Role of Endoplasmic Reticulum Stress in Otitis Media - Zhao, Hongchun; Wang, Yanfei; Li, Bo; Zheng, Tihua; Liu, Xiuzhen; Hu, Bo Hua; Che, Juan; Zhao, Tong; Chen, Jun; Hatzoglou, Maria; Zhang, Xiaolin; Fan, Zhaomin; et al. (Frontiers in Genetics, 2020)
Endoplasmic reticulum (ER) stress occurs in many inflammatory responses. Here, we investigated the role of ER stress and its associated apoptosis in otitis media (OM) to elucidate the mechanisms of OM and the signaling crosstalk between ER stress and other cell damage pathways, including inflammatory cytokines and apoptosis. We examined the expression of inflammatory cytokine- and ER stress-related genes by qRT-PCR, western blotting, and immunohistochemistry (IHC) in the middle ear of C57BL/6J mice after challenge with peptidoglycan polysaccharide (PGPS), an agent inducing OM. We also evaluated the effect of the suppression of ER stress with tauroursodeoxycholic acid (TUDCA), an ER stress inhibitor. The study revealed the upregulation of ER stress- and apoptosis-related gene expression after the PGPS treatment, specifically, ATF6, CHOP, BIP, caspase-12, and caspase-3. TUDCA treatment of PGPS-treated mice, decreased OM, reduced the expression of CHOP, BIP and caspase 3, and significantly decreased the proinflammatory gene expression of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6). These results suggest that PGPS triggers ER stress and downstream proinflammatry gene expression in OM and that inhibition of ER stress alleviates OM. We propose that ER stress plays a critical role in inflammation and cell death, leading to the development of OM and points to ER stress inhibition as a potential therapeutic approach for the prevention of OM.